Plant Phenolics and Extracts in Animal Models of Preeclampsia and Clinical Trials-Review of Perspectives for Novel Therapies - Marcin Ożarowski; Tomasz M. Karpiński; Michał Szulc; Karolina Wielgus; Radosław Kujawski; Hubert Wolski; Agnieszka Seremak-Mrozikiewicz (MDPI AG, 2021)
The current health requirements set the direction in pharmacological research, especially as regards diseases that require improvement of existing therapeutic regimens. Such diseases include preeclampsia, which is a hypertensive disorder of pregnancy during which there occurs progressive increasing activation of the immune system through elevation of pro-inflammatory cytokines and antiangiogenic factors, which is dangerous for the mother and fetus. A promising field of research for new drugs to treat this disease is the study of natural phenolic compounds of plant origin and herbal extracts, which are complex matrices of chemical compounds with broad biological activities. Many plant substances with anti‑inflammatory and anti‑hypertensive properties are known, but studies in animal models of preeclampsia and clinical trials concerning this disease constitute a new and developing research trend of significant medical importance. The aim of our research review was to identify and analyze the results of already available studies on baicalin, curcumin, epigallocatechin gallate, punicalagin, quercetin, resveratrol, salvianolic acid A (danshensu), silibinin, and vitexin, as well as plant extracts from Brassica oleracea L., Euterpe oleracea Mart., Moringa oleifera Lam., Punica granatum L., Silybum marianum (L.) Gaertner, Thymus schimperi Ronniger, Uncaria rhynchophylla (Miq.) Miq. ex Havil., and Vitis vinifera L., which are potential and promising candidates for further research and for potential new therapies.